Analisis Kemampuan Kreativitas Siswa Berbasis Proyek Energi Terbarukan Berbantuan Model Pembelajaran Project Based Learning pada Kurikulum Merdeka - Tatsar, Mohammad Zaky; Rohman, Daniel Cholilur; Salamah, Umu (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2023)
Abstract: The main problem in this study is that class X students have several obstacles experienced by students in absorbing lessons. For example, students get bored quickly when absorbing lessons, fall asleep easily, and talk to friends outside of their study topics. This study aims to determine whether students' creative abilities increase by analyzing students' creative abilities based on renewable energy projects in the independent curriculum at SMA Negeri 1 Gondangwetan. The type of research used by researchers is a type of Quasi-Experimental Design research. The research method used is quantitative. The population in this study were students of class X SMA Negeri 1 Gondangwetan, totaling 10 classes, and samples were taken from the population, namely class X-1 and X-7 as the experimental class. Data on students' creative abilities were obtained from administering student creativity tests and from student creativity sheets. The data analysis technique that the researchers used was the t-test. The results of data analysis (a) the results of student completeness in each indicator of student creativity can be seen that applying the Project Based Learning model in the independent curriculum can increase student creativity. This result is evidenced by the percentage of completeness in class X-1 on the indicators of fluent thinking skills by 34% and class X-7 by 34%, indicators of flexible thinking skills in class X-1 by 25% and class X-7 by 19.66%, indicators of original thinking in class X-1 by 24% and class X-7 by 22.33%, indicators of detailing skills in class X-1 by 29% and class X-7 by 31.33%, indicators of assessing skills for class X -1 by 32% and class X-7 by 33%. (b) The average result through the t-test is that the p-value with df 35 is less than 0.05 (p=0.00 0.05), thus H_1 is accepted and H_0 is rejected. Based on the results of this study, it shows that analyzing students' creative abilities with the help of project-based learning models in the independent curriculum can increase student creativity.Keywords: Student creativity, project-based learning, independent curriculumAbstrak: Permasalahan utama dalam penelitian ini adalah siswa kelas X memiliki beberapa kendala yang dialami dalam menyerap pelajaran. Misalnya siswa cepat bosan saat menyerap pelajaran, mudah tertidur, berbicara dengan teman di luar topik yang dipelajarinya. Penelitian ini bertujuan untuk mengetahui apakah kemampuan kreatif siswa meningkat dengan menganalisis kemampuan kreatif siswa berbasis proyek energi terbarukan dalam kurikulum mandiri di SMA Negeri 1 Gondangwetan. Jenis penelitian yang digunakan oleh peneliti adalah jenis penelitian Quasi Experimental Design. Metode penelitian yang digunakan adalah kuantitatif. Populasi dalam penelitian ini adalah siswa kelas X SMA Negeri 1 Gondangwetan yang berjumlah 10 kelas dan sampel diambil dari populasi yaitu kelas X-1 dan X-7 sebagai kelas eksperimen. Data kemampuan kreatif siswa diperoleh dari penyelenggaraan tes kreativitas siswa dan dari lembar kreativitas siswa. Teknik analisis data yang peneliti gunakan adalah uji-t. Hasil analisis data diperoleh (a) hasil ketuntasan siswa pada setiap indikator kreativitas siswa dapat diketahui bahwa penerapan model pembelajaran berbasis proyek pada kurikulum mandiri dapat meningkatkan kreativitas siswa. Hasil ini dibuktikan dengan persentase ketuntasan kelas X-1 pada indikator keterampilan berpikir lancar sebesar 34% dan kelas X-7 sebesar 34%, indikator keterampilan berpikir luwes pada kelas X-1 sebesar 25% dan kelas X- 7 sebesar 19,66%, indikator berpikir orisinal pada kelas X-1 sebesar 24% dan kelas X-7 sebesar 22,33%, indikator keterampilan merinci pada kelas X-1 sebesar 29% dan kelas X-7 sebesar 31,33%, indikator menilai keterampilan untuk kelas X-1 sebesar 32% dan kelas X-7 sebesar 33%. (b) Hasil rata-rata melalui uji-t diperoleh nilai p dengan df 35 lebih kecil dari 0,05 (p=0,00 0,05). Berdasarkan hasil penelitian ini menunjukkan bahwa dengan menganalisis kemampuan kreatif siswa dengan bantuan model pembelajaran berbasis proyek pada kurikulum mandiri dapat meningkatkan kreativitas siswa.Kata-kata kunci: Kreativitas siswa, project-based learning, kurikulum merdeka